On the role of crystal-liquid interfacial energy in determining scaling, nucleation and crystal growth in membrane distillation crystallisation - Vasilakos, Konstantinos; Thomas, Navya; Hermassi, Mehrez; Campo Moreno, Pablo; McAdam, Ewan J. (Elsevier, 2025)
While the interfacial energy (σ) of a solute contributes toward the excess surface free energy requirement for nucleation, its role in determining scaling, nucleation and crystal growth processes within membrane distillation has yet to be described. Highly soluble salts (low σ) are generally understood to possess a low nucleation energy, where the limited relative supersaturation (Δc/c∗) can favour a heterogeneous primary nucleation mechanism. This was indicated by scaling, which is generally presumed to occur in response to the membrane substrate lowering the critical Gibbs free energy requirement for nucleation (ΔG∗). For less soluble salts (high σ), primary nucleation was not observed until Δc/c∗ exceeded a threshold of 1. It was postulated that the excess chemical potential available was sufficient to favour homogeneous primary nucleation in the bulk solution, which mitigates scale formation on the membrane. In-situ characterisation methods also established how nucleation rate and crystal size could be directly attributed to the σ, which is compatible with the crystallisation literature on aqueous salts within a comparable range of solubilities. While crystallisation tends to be controlled by a combination of thermodynamic and kinetic processes, this study illustrates how interfacial energy (a thermodynamic quantity) can be used to anticipate nucleation and crystal growth mechanisms in membrane crystallisation.
Keywords: Chemical Engineering; 40 Engineering; Generic health relevance; 34 Chemical sciences